Las prácticas de creación artística en el Urabá antioqueño. Patrimonio cultural inmaterial no visibilizado. (2011)
In order to understand the subject of the creator artist s invisibility in the Colombian context of the region of Urabá; Antioquia; it is a must to examine obliquely the social and historic particulars of a sub region located strategically with economic; ethnographic and cultural dynamics; which have emerged from the ongoing fight for a vast and ecologically abundant territory. With approximately a 50% of African descent population; a 15% of indigenous population an 35% of mestizos ; the sub region has created an interesting intercultural view; privileged to have artistic expressions for which its creators are not particularly visualized through the public politics that concern the State of Colombian.